2022
DOI: 10.1039/d2ta06064g
|View full text |Cite
|
Sign up to set email alerts
|

Ag2Se/nylon self-supporting composite films for wearable photo-thermoelectric generators with high output characteristics

Abstract: Recently, the skyrocketing interest in smart wearable devices has led to innovations in energy-harvesting materials. Flexible thermoelectric (TE) materials have thus developed rapidly, but in this process TE performances have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…Figure f displays the contactless perception capabilities of the proposed E-skins, which were evaluated at distances ranging from 1 to 10 mm. Photothermal Ag 2 Se at the sensing end of the E-skin absorbs the heat radiation, creating a temperature difference with the reference end due to its asymmetrical design (Figure S10); therefore, the electrical signal can be detected . This feature is expected to serve as a data input interface for remote sensing and virtual reality. Apart from the above features, sensing ambient light, including ultraviolet (UV), visible light, and infrared (IR), is another important function of artificial human sensory systems, as overexposure to UV or IR light can be harmful to the human body …”
Section: Resultsmentioning
confidence: 99%
“…Figure f displays the contactless perception capabilities of the proposed E-skins, which were evaluated at distances ranging from 1 to 10 mm. Photothermal Ag 2 Se at the sensing end of the E-skin absorbs the heat radiation, creating a temperature difference with the reference end due to its asymmetrical design (Figure S10); therefore, the electrical signal can be detected . This feature is expected to serve as a data input interface for remote sensing and virtual reality. Apart from the above features, sensing ambient light, including ultraviolet (UV), visible light, and infrared (IR), is another important function of artificial human sensory systems, as overexposure to UV or IR light can be harmful to the human body …”
Section: Resultsmentioning
confidence: 99%
“…The flexible TE device used in this study is one that has been reported by us, 37 and the specific parameters are as follows: the device consists of four legs with length, width, and thickness of 16 mm, 4 mm, and 75 μm, respectively. The power factor and figure of merit (ZT) of the TE legs are 874.3 μW m −1 K −1 and 0.32.…”
Section: Preparation Of the Pcc For The Ptegmentioning
confidence: 99%
“…The method includes two main steps: (1) Ag 2 Se nanowires (NWs) were synthesized using Se NWs as a template; (2) the NWs were vacuum-filtrated on nylon and then hot-pressed at 200 °C. Since then, flexible Ag 2 Se films have received increasing attention, and much progress has been made in recent years. We have also done a series of improvements based on the flexible Ag 2 Se films. For instance, by increasing the reaction temperature for the synthesis of Ag 2 Se NWs from RT to 40 °C and other preparation processes being consistent with those in ref , an Ag 2 Se film was prepared with improved PF up to ∼1882 μW m –1 K –2 . Interestingly, Se nanoinclusions were observed in the film .…”
Section: Introductionmentioning
confidence: 97%